Meta-Analysis of the Numbered Head Together Learning Model on Learning Motivation and Comparison of Its Effectiveness at the Elementary to Senior High School in Indonesia - Muzayyin, Muhammad Dzuhri; Syahputra, Nurdian; Aini, Dewi Khurun (PALAPA, 2024)
Learning motivation becomes a driving force that exists from within and outside students, thus causing desire and enthusiasm in learning to achieve a goal. However, not all students have high motivation in their studies to produce academic achievements. To overcome the problem of low student learning motivation, researchers are trying to find the right solution. And the NHT type cooperative learning model is a solution as a learning model that can motivate students to learn actively, creatively, and critically in teaching and learning activities. This research is a type of meta-analysis research that summarizes similar research relevant to the topic and then draws a general conclusion. The software used in data analysis is JASP. The results of the analysis of the summary effect using a random effect model showed that there was a positive influence of the NHT learning model on student learning motivation with an estimate score of 0.841. It can be concluded that the Numbered Head Together (NHT) learning model has an effect on increasing student learning motivation because it can be seen from the results of 14 studies analyzed using meta-analysis to get a mean effect size of 0.841 or an effect of 84%. In analyzing the moderation effect of educational levels, elementary schools (SD) rank first with an effect size of 1.513 and a Q value of 24.85. Senior high schools (SMA) rank second with an effect size of 0.841 and a Q value of 125.384. Lastly, junior high schools (SMP) rank third with an effect size of 0.557 and a Q value of 45.209. It can be concluded that the effectiveness of the NHT model depends on the educational level.